The role of social media in improving digital literacy among the Sei Mencirim Village Community, Sunggal District - Dasa Syawal Syahputra (Jurnal Mandiri IT, 2026)
Social media is a technological advancement that has become inseparable from modern society. Various benefits have been experienced by the public following the emergence of social media in their daily lives. However, the question remains whether social media has played a positive role in society, particularly in rural communities. This article aims to explore more deeply the role of social media in improving digital literacy among the community in Sei Mencirim Village, Sunggal District. This study employs a qualitative method, with data collected through observations and interviews with residents of Sei Mencirim Village, Sunggal District. The results of this study indicate that social media has contributed to enhancing digital literacy among the community in Sei Mencirim Village, Sunggal District. This is reflected in the community’s good understanding of digital literacy as well as their awareness of not indiscriminately sharing information obtained from social media. However, the amount of content related to digital literacy available across various social media platforms remains limited. Therefore, the government needs to encourage content creators to more actively and extensively produce such content.